Short interest and corporate investment: Evidence from supply chain partners - CHEN, Xia (Institutional Knowledge at Singapore Management University, 2022)
Short interest contains valuable information about a firm’s business fundamentals. We investigate whether such information affects business partners’ real investment decisions in the supply-chain setting. We predict and find that a supplier’s future investments (including inventory, R&D, and tangible asset investments) decrease with its customer’s current short interest. This negative relation is stronger when the supplier faces greater difficulty in assessing its customer’s business fundamentals and when short interest is more likely to indicate longlasting deterioration in the customer’s fundamentals. Additional analysis does not support the alternative explanation that the supplier adjusts investments in response to unfavorable information obtained via private communication with its customer. We also find that suppliers who are more responsive to the customers’ short interest in reducing investments experience weaker wealth transfer from these customers and better investment efficiency. Overall, our evidence suggests that customers’ short interest has significant information value in facilitating suppliers’ investment decisions, and suppliers who adjust their investments based on such information enjoy greater economic benefits.